Surface crack closing method for the carbon composite bipolar plates of a redox flow battery. (January 2015) - Kim, Ki Hyun; Choe, Jaeheon; Nam, Soohyun; Kim, Bu Gi; Lee, Dai Gil
Abstract: The vanadium redox flow battery (VRFB) is the most promising energy storage system (ESS) due to its safety, durability and scalability. The electrode and the bipolar plate are the most important components that affect the efficiency of the VRFB. Based on previous research, an expanded graphite-coating method for the composite bipolar plate of the VRFB was employed to reduce interfacial contact resistance between the electrode and the bipolar plate. However, damage to the coating layer of the composite bipolar plate during actual operating condition can reduce durability of the composite bipolar plate. In this work, a surface crack closing method for the damaged composite bipolar plates of a redox flow battery was developed. To optimize the surface crack closing process, compressive tests of the expanded graphite were performed. The effect of the surface crack closing process was estimated by measuring the area-specific resistance (ASR) before and after an electro-chemical operation test. Based on the results of the analysis, the optimal surface crack closing process for the composite bipolar plate was suggested.